MEKANISME PENYELESAIAN KONFLIK TRADISIONAL SUKUBANGSA MOI (Traditional Solution of Conflict in Moi Tribe) - Yudha N Yapsenang; Desy P Usmany (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2019)
The Moi people are one of the ethnic groups within the Bomberay customary territory. In the past, in the culture of Moi ethnicity to solve various problems that occur in their social and cultural life, it has been agreed that together several mechanisms for resolving conflicts / disputes / disputes, namely blessing and recitation of foo. Both of these mechanisms in the past were very sacred, so that the results obtained were able to answer or resolve problems or conflicts that occurred in the community, and were able to guarantee harmony in life in the community. ABSTRAKSuku bangsa Moi merupakan salah satu sukubangsa yang berada dalam wilayah adat Bomberay. Di masa lampau dalam budaya sukubangsa Moi untuk menyelesaikan berbagai permasalahan yang terjadi dalam kehidupan sosial budaya mereka telah disepakati secara bersama-sama beberapa mekanisme penyelesaian konflik/pertikaian/perselisihan, yaitu teh bless dan kalak foo. Kedua mekanisme ini dimasa lampau sangat sakral, sehingga hasil yang diperoleh mampu menjawab atau menyelesaikan permasalahan atau konflik yang terjadi dalam masyarakat, serta mampu menjamin keharmonisan hidup dalam masyarakat.